Efficiencies of arbuscular mycorrhizal fungi for agro-sustainable production on livestock farms - Alexander Pérez Cordero; Donicer E.Montes Vergara; Yelitza Aguas Mendoza (International Journal of Medical Toxicology and Legal Medicine, 2024)
The objective was to evaluate in the field the efficiency of native arbuscular mycorrhizal fungi associated with forage production in the grass species Bothriochloa pertusa (L) A. Camus in livestock farms in the municipality of Corozal, department of Sucre, Colombia. The work consisted of three stages: laboratory, greenhouse and on-farm efficiency test. During the on-farm efficiency test, the production of green forage, dry matter, nutritional content of the grass species, spore density and infection percentage were evaluated. The number of spores/100 g soil and the percentage of root infection found on the cattle farms ranged from 2600 and 41 - 65 respectively. 23 morphospecies were isolated of arbuscular mycorrhizal fungi were isolated, distributed in two genera Glomus and Gigospora, with species of the genus Glomus predominating. The 8 morphotypes evaluated in the greenhouse showed different degrees of colonization on Brachiaria decumbens roots. Morphospecies 5, 18 and 22 showed the highest spore densities/ 100 grams of soil. The results show that the morphotypes tested in sterile soils showed high efficiency in forage production in colosoana grass, high phosphorus concentration in plant tissues, high spore density and percentage of colonization in roots, results very similar to the effects of the mixture of morphotypes in natural soils